Influence of mechanical errors in a zoom camera - Gardel, Alfredo (Image analysis and stereology, 2003)
As it is well known, varying the focus and zoom of a camera lens system changes the alignment of the lens components resulting in a displacement of the image centre and field of view. Thus, knowledge of how the image centre shifts may be important for some aspects of camera calibration. As shown in other papers, the pinhole model is not adequate for zoom lenses. To ensure a calibration model for these lenses, the calibration parameters must be adjusted. The geometrical modelling of a zoom lens is realized from its lens specifications. The influence on the calibration parameters is calculated by introducing mechanical errors in the mobile lenses. Figures are given describing the errors obtained in the principal point coordinates and also in its standard deviation. A comparison is then made with the errors that come from the incorrect detection of the calibration points. It is concluded that mechanical errors of actual zoom lenses can be neglected in the calibration process because detection errors have more influence on the camera parameters.
Keywords: Kalibracija; Pattern Recognition; Slika, obdelava z računalnikom; Calibration; Image Processing, Computer-Assisted; Vzorec, razpoznavanje; optika; povečave; napake